The Effects of Expertise on the Hindsight Bias. (29th March 2016) - Knoll, Melissa A. Z.; Arkes, Hal R.
Abstract: We present data from three experiments examining the effects of objective and subjective expertise on the hindsight bias. In Experiment 1, participants read an essay about baseball or dogs and then answered questions about the baseball essay to the best of their ability, as if they had not read the essay, or to the best of their ability, although they read about dogs. Participants also completed a quiz about baseball rules and terminology, which was an objective measure of expertise. Results demonstrated that as participants' baseball expertise increased, their inability to act as if they never read the essay also increased; expertise exacerbated the hindsight bias. To test the effects of subjective expertise on hindsight bias and investigate factors underlying the relationship, participants in Experiment 2 ranked five topics in order of expertise and gave feeling‐of‐knowing (FOK) ratings for questions from these topics. Foresight participants then saw each question again and answered the questions; hindsight participants saw the questions and answers and gave the probability they would have known the answers had they not been provided. Hindsight bias increased with subjective expertise as did average FOK ratings. In Experiment 3, we experimentally manipulated perceived expertise but found that neither average FOK ratings nor hindsight bias was affected by experimentally induced expertise. Taken together, the results demonstrate that expertise exacerbates both objective and subjective hindsight bias but that an FOK, which likely exists only when expertise is naturally acquired, is necessary to engender the detrimental effect of expertise on the hindsight bias. Copyright © 2016 John Wiley & Sons, Ltd.